The Duties of a Pupil: the Implementation Problem - Kairienė, Brigita (Pedagogika, 2017)
On the basis of a prevailing perception that children are well aware of their rights, however, do not know their duties, the article examines the problem of the implementation of the duties of a pupil in general education schools. Through the use of quantitative research, it is sought to determine what duties of pupils are defined by the Rules for Pupils of general education schools and what possibilities of their implementation are. It has been established that the rules of pupils defined by the Rules for Pupils are linked to the requirement to behave in a certain way in accordance with the norms of a value-based behaviour, i. e. to respect others, to behave and learn in a cultured way, courteously, and the requirement to avoid certain behaviour while identifying actions, hindering a learning process and actions which hurt the dignity of other persons. The implementation of the duties described by the Rules for Pupils which are linked to the compliance with value-based attitudes casts doubts, because when defining the duties of pupils the development of a child has not been taken into account, i. e. duties have not been distinguished according to the age of a child. In addition, an equal educational relationship between an educator and an educate is violated – the rules for pupils include exceptional requirements, which have to be adhered, regarding teachers – teachers are singled out as a social group worthy of particular respect in comparison with other members of a school community. The implementation of the duties of a pupil is also limited by the possibility to know the criteria of a value-based behavior which are not defined. Therefore, it is a concern that, in response to the failure to meet norms of a value-based behaviour, sanctions are endorsed, which are not even distinguished according to characteristic of failure to comply with responsibilities.